AN OBSERVATIONAL STUDY OF 14 NEONATES WITH SCRUB TYPHUS - Dr. C. Mary Reena; Dr. J. Ashok Raja; Dr. Shetty Subhodh Sivarama; Dr. D. S. Jothi (Journal of Population Therapeutics and Clinical Pharmacology, 2023)
Scrub typhus is a rickettsial infection causing pneumonia, myocarditis, bone marrow suppression, Disseminated Intravascular Coagulation and multi-organ failure. Presentation in neonates is rare. We conducted this study on neonates diagnosed as scrub typhus, discuss their clinical presentation and review the literature. The neonates admitted in a tertiary care centre with clinical diagnosis of sepsis were enrolled for the study. Clinical presentation, epidemiology, risk factors, laboratory findings and treatment were recorded. Diagnosis was confirmed by IgM ELISA test and the clinical response to Doxycycline was noted. Anemia, thrombocytopenia and coagulopathy were seen in all neonates. Eschar was not noticed in these cases. Mortality was high (57.1%). Scrub typhus, a sepsis mimicker needs early evaluation and a trial of Doxycycline in suspected neonates my save lives. Polymerase Chain Reaction confirmation and epidemiological surveillance is necessary to standardize antibody kits and controlling endemic.